Cyclic-di-GMP Regulates Autoaggregation Through the Putative Peptidoglycan Hydrolase, EagA, and Regulates Transcription of the znuABC Zinc Uptake Gene Cluster in Erwinia amylovora - Kharadi, Roshni R.; Sundin, George W. (Frontiers in Microbiology, 2020)
Erwinia amylovora is the causal agent of fire blight, an economically impactful disease that affects apple and pear production worldwide. E. amylovora pathogenesis is comprised of distinct type III secretion-dependent and biofilm-dependent stages. Alterations in the intracellular levels of cyclic-di-GMP (c-di-GMP) regulate the transition between the different stages of infection in E. amylovora. We previously reported that hyper-elevation of c-di-GMP levels in E. amylovora Ea1189, resulting from the deletion of all three c-di-GMP specific phosphodiesterase genes (Ea1189ΔpdeABC), resulted in an autoaggregation phenotype. The two major exopolysaccharides, amylovoran and cellulose, were also shown to partially contribute to autoaggregation. In this study, we aimed to identify the c-di-GMP dependent factor(s) that contributes to autoaggregation. We conducted a transposon mutant screen in Ea1189ΔpdeABC and selected for loss of autoaggregation. Our search identified a peptidoglycan hydrolase, specifically, a D, D-endopeptidase of the metallopeptidase class, EagA (Erwinia aggregation factor A), that was found to physiologically contribute to autoaggregation in a c-di-GMP dependent manner. The production of amylovoran was also positively affected by EagA levels. An eagA deletion mutant (Ea1189ΔeagA) was significantly reduced in virulence compared to the wild type E. amylovora Ea1189. eagA is part of the znuABC zinc uptake gene cluster and is located within an operon downstream of znuA. The znuAeagA/znuCB gene cluster was transcriptionally regulated by elevated levels of c-di-GMP as well as by the zinc-dependent transcriptional repressor Zur. We also observed that with an influx of Zn2+ in the environment, the transcription of the znuAeagA/znuBC gene cluster is regulated by both Zur and a yet to be characterized c-di-GMP dependent pathway.